Sexual Violence a Victim Survey in a National Sample of Female College Students and Graduates - Kayı, Zehra; Yavuz, Mehmet Fatih; Arıcan, Nadir (The Bulletin of Legal Medicine, 2000)
Our study aims to enlighten the detailed information about sexual violence acts toward female university students and graduates in Turkey. This research of sexual violence victim survey includes the rates of sexual violence acts, when, where, by whom and how being acted, how effected the victims and finally reasons of non-reporting. The research was performed among 700 female participants including both university students and graduates in Istanbul. Mean age was 22.3 years. Results have shown that females were highly exposed to sexual violence and the assailants were commonly acquaintance of the victims. Incidence of sexual violence was high and reporting ratio was very low. Being exposed to any kind of sexual violence was seen in 84 % of females. Apart from the verbal and visual ones, being a victim of sexual violence conducted by physical contact to body parts with a range of bad touch to rape was also seen in high levels such as in -44.8 %. Besides the high rates of victimization, the low rates of reporting especially signifies the importance of forensic medical efforts to perform affective medical examination and also the evaluation of evidences in order to overcome this problem.Key Words: Sexual violence, female, victim.
Keywords: sexual violence; female; victim